Discovery of novel 5-hydroxy-4-pyridone-3-carboxy acids as potent inhibitors of influenza Cap-dependent endonuclease. Issue 19 (1st October 2016) - Miyagawa, Masayoshi; Akiyama, Toshiyuki; Mikamiyama-Iwata, Minako; Hattori, Kazunari; Kurihara, Naoko; Taoda, Yoshiyuki; Takahashi-Kageyama, Chika; Kurose, Noriyuki; Mikamiyama, Hidenori; Suzuki, Naoyuki; Takaya, Kenji; Tomita, Kenji; et al.
Graphical abstract: Abstract: We report the discovery of a novel series of influenza Cap-dependent EndoNuclease (CEN) inhibitors based on the 4-pyridone-carboxylic acid (PYXA) scaffold, which were found from our chelate library. Our SAR research revealed the lipophilic domain to be the key to CEN inhibition. In particular, the position between the chelate and the lipophilic domain in the derivatives was essential for enhancing the potency. Our study, based on virtual modeling, led to the identification of2y as a potent CEN inhibitor with an IC50 of 5.12 nM.